A influência da cultura nas negociações. Estudo de caso: aquisição de uma empresa brasileira por uma empresa alemã - Abreu, Letícia Vasconcellos (Universidade do Vale do Rio dos Sinos, 2012)
This paper aims to explore the cultural questions involved with the acquisition of a logistic Brazilian company by a German company, as well as the influence of culture on the negotiation itself. This analysis starts with Hofstede’s and Schein’s theories about cultural issues, as well as the differences between German and Brazilian cultures. As expected, both the extent to which Brazilians are acquainted with the German culture and vice versa, and the main stereotypes concerning each people were also considered. In order to contextualize the whole acquisition, both the background of the logistic field in Brazil, and its short-term perspectives, were summarized. The same was done to other relevant issues, such as the description of the seller company as a family-owned company and a short report on the phases an acquisition usually comprises. In order to analyze the negotiation itself, two executives representing both the buyer and the seller companies were interviewed and asked about their impressions about the acquisition process, their motivations for doing business and their views about each other’s side. In the end, conclusions are presented, in which cultural differences between Brazil and Germany were not so outstanding as it could be expected. This could be due to the fact that, in this specific case, both sides were already used to international negotiations, and there was also some similarity between both cultures involved in the process. Besides that, other factors that are integrating parts of an acquisition and a company’s own culture also influenced negotiation procedures and results.
Keywords: Cultura; Negociação Internacional; Logística; Aquisição de Empresas; Culture; International Negotiation; Logistics; Acquisition